2016
DOI: 10.1371/journal.pone.0148715
|View full text |Cite
|
Sign up to set email alerts
|

Oral Implant-Prostheses: New Teeth for a Brighter Brain

Abstract: Several studies have demonstrated that chewing can be regarded as a preventive measure for cognitive impairment, whereas masticatory deficiency, associated with soft-diet feeding, is a risk factor for the development of dementia. At present the link between orofacial sensorimotor activity and cognitive functions is unknown. In subjects with unilateral molar loss we have shown asymmetries in both pupil size and masticatory muscles electromyographic (EMG) activity during clenching: the molar less side was charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 73 publications
2
46
1
3
Order By: Relevance
“…Fibers from trigeminal nuclei could affect the distal dendrites of the pericoerulear region ( Aston-Jones et al, 1986 , 1991 ), as well as, via the paragigantocellularis and the prepositus hypoglossi nuclei ( Lovick, 1986 ; Buisseret-Delmas et al, 1999 ), the LC cell bodies ( Aston-Jones et al, 1986 ). So, an increase in LC activity could occur during the trigeminal-induced enhancements in task-related mydriasis and in cognitive performance (see De Cicco et al, 2014 , 2016 ), which would benefit of the release of noradrenaline at cerebral cortical level ( Gabay et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibers from trigeminal nuclei could affect the distal dendrites of the pericoerulear region ( Aston-Jones et al, 1986 , 1991 ), as well as, via the paragigantocellularis and the prepositus hypoglossi nuclei ( Lovick, 1986 ; Buisseret-Delmas et al, 1999 ), the LC cell bodies ( Aston-Jones et al, 1986 ). So, an increase in LC activity could occur during the trigeminal-induced enhancements in task-related mydriasis and in cognitive performance (see De Cicco et al, 2014 , 2016 ), which would benefit of the release of noradrenaline at cerebral cortical level ( Gabay et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pupillographic measurements have been previously used to indirectly track the activity of LC neurons ( Silvetti et al, 2013 ; Hoffing and Seitz, 2015 ; Kihara et al, 2015 ; Hayes and Petrov, 2016 ; see also Laeng et al, 2013 ; De Cicco et al, 2014 , 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recent experiments have shown that the presence of a sensorimotor trigeminal imbalance (related to occlusal problems)—consisting in an asymmetric activation of masseter muscles during clenching—is strongly correlated to an asymmetry in pupils size, either in the normal jaw resting position, with the arches few millimetres apart, or with the teeth in contact (De Cicco et al, 2014 , 2016 ). Since pupil size is considered as a reliable indicator of LC activity and its asymmetry is strongly reduced following removal of the trigeminal imbalance by occlusal correction, these data suggest that the trigeminal imbalance makes the LC discharge asymmetric.…”
Section: Trigeminal Visceral and Vestibular Influences On Brain Funcmentioning
confidence: 99%
“…An alteration of this balance due to central or peripheral phenomena, such as an alteration in the occlusion [ 106 108 ], may induce a state of CS at this level, in part justifying the hyperarousal state in CSSs. LC has been also linked to a category of disorders characterized by imbalance of the arousal systems and alteration of tonic-phasic function of the LC, including disorders of affective-emotional sphere [ 109 ], chronic pain disorders [ 110 , 111 ], and migraine [ 112 , 113 ].…”
Section: Tens (Transcutaneous Electric Nerve Stimulation)mentioning
confidence: 99%